2006
DOI: 10.2514/1.19251
|View full text |Cite
|
Sign up to set email alerts
|

Some Recommendations for Characterization of Composite Panels by Means of Drop Tower Impact Testing

Abstract: Instrumented drop tower impact-test devices have been long used for inflicting impact damage onto test specimens for damage tolerance characterization of composite panels. However, there are many considerations that need to be made regarding the test setup to avoid the inconveniences related to the acquisition and interpretation of the impact data. Because there are many advantages associated with this type of experiment, to benefit fully from the amount of information available from an impact test, a multipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 13 publications
(36 reference statements)
2
42
0
Order By: Relevance
“…This manifested as a more severe impact damage and smaller F max and a shorter t c than those of the original C/BMI composite in Region II. As reported by Feraboli [36], a smaller F max with a longer t c is a result of more compliant combinations of impactor-target in the case of thin laminates, which indicates a reduction of the resistance to impact loading of C/BMI composite caused by 300 cycles. Additionally, the absorbed energy is significantly higher in the cycled C/BMI composite than in the original one, but the increase in the ratio of absorbed energy is much smaller than that of damage area in Region II.…”
Section: Damage Characteristicssupporting
confidence: 52%
See 1 more Smart Citation
“…This manifested as a more severe impact damage and smaller F max and a shorter t c than those of the original C/BMI composite in Region II. As reported by Feraboli [36], a smaller F max with a longer t c is a result of more compliant combinations of impactor-target in the case of thin laminates, which indicates a reduction of the resistance to impact loading of C/BMI composite caused by 300 cycles. Additionally, the absorbed energy is significantly higher in the cycled C/BMI composite than in the original one, but the increase in the ratio of absorbed energy is much smaller than that of damage area in Region II.…”
Section: Damage Characteristicssupporting
confidence: 52%
“…12). In a previous study, Xu [37] found that there exists an interaction between matrix cracking and free-edge delamination in a glass fiber reinforced BMI composite laminates under static tension. It was shown that matrix cracking could lead to local free-edge delamination and free-edge delamination might induce matrix cracking.…”
Section: Impact Damage Model and Degradation Mechanismmentioning
confidence: 96%
“…The characteristic parameters include F i , F p , D i , D p , D max , E d , E el , the definitions of which are also found in the literature [16,17]. E d2 was also adopted in the discussion of impact properties in this study.…”
Section: Impact Testing Resultsmentioning
confidence: 99%
“…In many cases, these damages are initiated inside the structure and therefore usually go unnoticed. Process parameters such as contact force, energy and projectile deflection, values of which are normally gathered during an impact testing event, are useful for the comparison of the impact properties of laminated composites [15][16][17]. The influence of hygrothermal conditioning on the capacity of PMCs to resist impact loading, however, has not received enough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumented drop-weight tests are very popular because they are simple to perform and easily repeatable [19]. The principal measurement in these tests is the load-time history, which can be integrated to produce the displacement and absorbed energy of the impacted plate.…”
Section: Impact Damage Resistance 221 Impact Testingmentioning
confidence: 99%